The Participatory and Responsiveness of Local Budget Policy in Malang, Indonesia - Salahudin Salahudin; Vissanu Zumitzavan; Achmad Nurmandi; Tri Sulistyaningsih; Kisman Karinda (Otoritas : Jurnal Ilmu Pemerintahan, 2019)
Since political reform in 1998, the Indonesian government has decentralized governance practices in order to provide a space for local governments to develop the local potential of each region. Consequently, the local government should be responsive to people’s needs and more accountable for regional development. Therefore, local governments should be willing to involve local citizens in the public policy-making process. On the other side, local communities should actively engage in development processes, particularly in budget policy planning. This article reports on a study to determine to what extent the local government is responsive and accountable to the local citizens in Malang Municipality in Indonesia. A qualitative approach was applied to the process of data collection and data analysis. The results show that the local government has low responsiveness and accountability to local citizen’s needs and local preferences. The findings reveal a lack of willingness on the part of local government to involve local citizens and civic groups in budget planning, and elected officials demonstrate little responsibility in arranging budget policy support to achieve social welfare, one of the main points of decentralization. These findings show that central government should pay more attention to improving the awareness of local governments and the capacity of local communities so that decentralization may be supported.